Seizure Occurring During Baclofen Monotherapy for Phenibut Withdrawal. Issue 2 (4th March 2023) - Patt, Amber; Fox, Haley; Wells, Lauren; Theobald, Jillian; Feldman, Ryan
Abstract : Objective: Phenibut is a widely available gamma-aminobutyric acid B receptor agonist. When taken chronically, phenibut causes dependence and subsequent withdrawal if stopped. Baclofen, a gamma-aminobutyric acid B receptor agonist structurally related to phenibut, has been used to manage phenibut withdrawal (PW), although baclofen doses for PW are not well defined and may exceed Food and Drug Administration–approved doses. Little data described outcomes from baclofen use. Methods: This case details a patient who experienced a seizure while on baclofen 10 mg thrice daily as monotherapy for PW and highlights a potential risk of underdosing baclofen as monotherapy in the management of PW. Results: A man in his early 30s with anxiety, depression, and substance use disorder presented to the emergency department by family for lethargy and confusion starting earlier that day. He had been using 25–30 g of phenibut daily for the past 6 months. On arrival, he was hypertensive, tachycardic, tachypneic, and lethargic. The patient received 1 mg of intravenous lorazepam and was admitted to the hospital for presumed PW. His symptoms improved overnight, and he was discharged on 10 mg of baclofen thrice daily. He returned 28 hours later after having a seizure and required intensive care admission in addition to multimodal drug therapy. Conclusions: Phenibut use is rising, and treatment options for PW, such as baclofen, warrant additional study. Potential risks of underdosing baclofen if used as monotherapy in PW may include seizures as withdrawal progresses. Baclofen's role in therapy may be more appropriate as an adjunct than a cornerstone of therapy. Treatment done in consultation with providers experienced in managing withdrawal such as a toxicologist may help reduce this risk.